In vitro Implementation of Photopolymerizable Hydrogels as a Potential Treatment of Intracranial Aneurysms - Poupart, Oriane; Schmocker, Andreas; Conti, Riccardo; Moser, Christophe; Nuss, Katja M.; Grützmacher, Hansjörg; Mosimann, Pascal J.; Pioletti, Dominique P. (Frontiers in Bioengineering and Biotechnology, 2020)
Intracranial aneurysms are increasingly being treated with endovascular therapy, namely coil embolization. Despite being minimally invasive, partial occlusion and recurrence are more frequent compared to open surgical clipping. Therefore, an alternative treatment is needed, ideally combining minimal invasiveness and long-term efficiency. Herein, we propose such an alternative treatment based on an injectable, radiopaque and photopolymerizable polyethylene glycol dimethacrylate hydrogel. The rheological measurements demonstrated a viscosity of 4.86 ± 1.70 mPa.s, which was significantly lower than contrast agent currently used in endovascular treatment (p=0.42), allowing the hydrogel to be injected through 430 µm inner diameter microcatheters. Photorheology revealed fast hydrogel solidification in 8 minutes due to the use of a new visible photoinitiator. The addition of an iodinated contrast agent in the precursor contributed to the visibility of the precursor injection under fluoroscopy. Using a customized light-conducting microcatheter and illumination module, the hydrogel was implanted in an in vitro silicone aneurysm model. Specifically, in situ fast and controllable injection and photopolymerization of the developed hydrogel is shown to be feasible in this work. Finally, the precursor and the polymerized hydrogel exhibit no toxicity for the endothelial cells. Photopolymerizable hydrogels are expected to be promising candidates for future intracranial aneurysm treatments.